Drought Risk Assessment Using Remote Sensing and GIS in Yemen - Ahmed Ali Dhaifallah, Ali; Bin MD. Hashim, Noorazuan; Bin Awang, Azahan (International Journal of Engineering and Technology, 2018)
Drought remains the most frequent and serious environmental threat in the Middle East area. In Yemen, drought has negatively been affecting both livelihood and sustainable development of the country. This research aims to monitoring and assessing the drought risk through the changes in vegetation cover and sand dunes deposit in Tihama Plain, Yemen using remote sensing and GIS. Landsat TM5 of 1985 and OLI8 of 2015 were used to evaluate the environmental indicators of drought using Normalized Difference Vegetation Index (NDVI) to recognize the progressive decline of vegetation based on the fact that vegetation absorbs red light and reflects infrared light of the electromagnetic spectrum. Through the index maps generated in a Geographic Information Systems (GIS) environment, the results showed that there was an increase of 26% in the area under severe drought during the period from 1985 to 2015. Similarly, the areas under moderate drought also increased to approximately 64%. On the other hand, areas under mild drought and those receiving normal rain experienced a decrease during the period as they gradually transformed into mild and severe drought situations. Within the study period, the area also recorded 74% increase in sand dunes deposit.Â Â